Antidepressant-like effects of Centella Asiatica (Pegaga) fresh extract on depression-induced rats / Nik Anis Amanina Nik Ayub - Nik Ayub, Nik Anis Amanina (2015)
Antidepressant-like effects of centella asiatica (pegaga) fresh extract on depression-induced rats centella asiatica is an herbaceous plant from family of apiaceae which has been used worldwide as medicine and consumed as traditional vegetables. Centella asiatica is reported to be useful for medicinal used such as memory enhancement, antidiabetic, antioxidant and antitumor. However, there is lack of studies done on effect of fresh centella asiatica extract as an antidepressant agent with two types which are small type and big type. Therefore, this study was conducted to determine the antidepressantlike effect of fresh centella asiatica (small type and big type) extract on depression induced rats in tail suspension test (tst) and forced swimming test (fst) through 14 days of orally administration. 42 male wistar rats were divided into four groups (one control group and three treatment group) with six rats in each group for both types of centella asiatica. All groups were kept under similar condition. Fresh centella asiatica extract were prepared in doses of 50, 100 and 200 mg/kg and administered orally for 14 consecutive days. Control group were being administered with distilled water. At the end of experiment, behaviour studies of rats models were observed. All three doses of fresh centella asiatica extract for both types in treatment group (50 mg/kg, 100 mg/kg and 200 mg/kg) were significantly reduced in immobility time in tst and fst as compared to the control group. However, the swimming and climbing duration for both types are significantly decreased as compared to control group which could provide false positive result in fst due to several factors such as depth of water level, strain of the animals and height of the tank. In a conclusion, centella asiatica (small type and big type) may possess antidepressant properties and can be used for anti-stress supplement.